Langerhans cell histiocytosis - Chauffaille, Maria de Lourdes L. F.; Valério, Rosana M.; Diniz, Cybelle Maria Costa; Simões, Milvia Maria; Enokihara, Silva; Michalany, Nylceo; Ferreira, Karin Ventura; Martinez, José Antonio Baddini; Hassun, Karine Marques; Atallah, Álvaro Nagib; Kerbauy, José (São Paulo Medical Journal, 1998)
The authors present a rare case of Langerhans cell histiocytosis in a 31 year old female patient with vulvar, peri-anal and oral lesions, diabetes insipidus, pulmonary skin and bone infiltrations. Skin biopsy immunohistochemistry presented positive S100 protein and vimentine, but the diagnosis was done with the demonstration of Birbeck granules with eletronic mucroscopy. The treatment was based on systemical chemotherapy although vulvar lesion has a bad response to chemotherapy.